(untitled) (Eureka Journal of Physical and Chemical Research, 2026)
The article describes in detail the effect of phytohormones on plant growth and development and its advantages, their environmental safety in the production of agricultural products, the ability to reduce energy consumption per unit of product, improve food quality, and the activity of phytohormones on plants.